Determination of the Toxicity Cause by Trace Metals on Zebrafish (Danio rerio) Embryo - D.P.N. De Silva; M.F.A. Fasmina; S. C. Jayamanne; N.P. P. Liyanage; J.L.C.S. Perera (Journal of Aquaculture and Fish Health, 2021)
Water quality deterioration due to inorganic and organic pollutant is a serious issue and the presence of toxic trace metals cause a serious threat to the aquatic ecosystem. Fish embryos have gained interest in risk assessment because of their high sensitivity to pollutants and the ecological relevance. This study investigated the acute toxicity effect of trace metals Arsenic (As), Cadmium (Cd), Mercury (Hg), Lead (Pb), Copper (Cu) and Zinc (Zn) on zebrafish (Danio rerio) embryo. Embryos were exposed to ten different concentrations of individual trace metals and lethality rate was recorded at 24, 48, 72 and 96 hours based on the coagulation of fertilized egg, lack of somite formation, lack of detachment of the tail and lack of heart beat. The results indicated a significant difference between the control and trace metal treated embryo (P< 0.05) and higher mortality rate along the increase of trace metal concentration. Along with the increase of exposure time for Cu, Zn and As, the  mortality rate became slower. Sub-lethal and teratogenic deformities such as growth retardation, lack of tail development, lack of eye lens (placode), yolk sac edema, pericardial edema, hemorrhages, shrinkage of chorion and scoliosis were observed in most of the trace metal treated embryos. The results showed the toxic effects to aquatic biota due to trace metals emphasizing the usefulness of zebrafish embryo model for integrated biological hazard assessment.